2014
DOI: 10.1074/jbc.m114.555870
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Protein Binding Motif within the T-synthase for the Molecular Chaperone Cosmc

Abstract: Background:We hypothesize that ER chaperone Cosmc binds specifically to its single client T-synthase. Results: Using molecular and biochemical approaches, we demonstrate that Cosmc recognizes a specific peptide within unfolded T-synthase. Conclusion: Cosmc-T-synthase interaction requires unique peptide recognition in the unfolded T-synthase that becomes inaccessible to Cosmc upon final folding. Significance: This study describes a novel peptide-specific chaperone recognition that regulates protein O-glycosylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 68 publications
1
15
1
Order By: Relevance
“…Cosmc is present in the ER of animal cells and has a single client protein, the T-synthase, to which it binds cotranslationally in the ER to prevent oligomerization and destruction in the proteasome. Successful binding of Cosmc to the T-synthase requires the presence of a novel CBRT (297), which is exposed in non-native T-synthase but becomes buried and inaccessible in the folded T-synthase. Once folded properly, the T-synthase moves to the Golgi apparatus, where it acts quantitatively on the products of the ppGalNAcTs to generate normal O -glycans (102).…”
Section: Figurementioning
confidence: 99%
“…Cosmc is present in the ER of animal cells and has a single client protein, the T-synthase, to which it binds cotranslationally in the ER to prevent oligomerization and destruction in the proteasome. Successful binding of Cosmc to the T-synthase requires the presence of a novel CBRT (297), which is exposed in non-native T-synthase but becomes buried and inaccessible in the folded T-synthase. Once folded properly, the T-synthase moves to the Golgi apparatus, where it acts quantitatively on the products of the ppGalNAcTs to generate normal O -glycans (102).…”
Section: Figurementioning
confidence: 99%
“…C. elegans and Drosophila T-synthase orthologs do not require Cosmc for proper folding, presumably due to the presence of N-glycans that were lost in mammalian T-synthase but may facilitate interaction with calnexin/calreticulin in the ER (Ju, Zheng, & Cummings, 2006). Mammalian Cosmc interacts with unfolded T-synthase, perhaps cotranslationally in the RER via a unique peptide region in T-synthase called the CBRT (Cosmc Binding Region of T-synthase; Aryal, Ju, & Cummings, 2014; Narimatsu et al, 2011). This results in proper folding of the T-synthase and production of an active enzyme, which is transported to the Golgi, preventing nonproductive aggregation, ubiquitination, retrotranslocation to the proteasome, and degradation (Ju, Aryal, et al, 2008).…”
Section: O-glycan Biosynthesismentioning
confidence: 99%
“…Previously, we found that hypermethylation of COSMC is one of the prevalent causes for the expression of the immature truncated O‐glycans (Tn and STn antigens) in ~40% of the PDAC tumours . Further, COSMC is the molecular chaperone for Core 1 synthase (C1GalT1) that stabilizes the enzyme . Loss of COSMC and aberrant expression of truncated O‐glycans induce oncogenic features, including compromised adhesion, increased cell migration, reduced apoptosis, loss of tissue architecture, invasive growth and metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…7 Further, COSMC is the molecular chaperone for Core 1 synthase (C1GalT1) that stabilizes the enzyme. 8 Loss of COSMC and aberrant expression of truncated O-glycans induce oncogenic features, including compromised adhesion, increased cell migration, reduced apoptosis, loss of tissue architecture, invasive growth and metastasis. 7,9 However, the molecular mechanism whereby these truncated O-glycans enhance the tumorigenic properties of PDAC cells remains elusive.…”
Section: Introductionmentioning
confidence: 99%